Jaminan Hak Pilih Warga Binaan Terhadap Keikutsertaan Dalam Pemilu Ditinjau Melalui Putusan MK 20/PUU-XVII/2019 - Nabila Azmi Rahmaningrum (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
The study is aimed at recognizing the share of non-citizen voting rights as an electoral ruling by mk 20/ puu-xvii /2019, the problem in this study is how protection and compensation of the people's voting rights in elections will be covered by an mk 20/ puu-xvii /2019 then how the election commission will play on the voting rights of the people. The study employed a normative study method using a constitutional and conceptual approach, a data source of primary and secondary data. Voting is a universal and inherent right within the duham, which basically claims that each citizen has the right to participate in the government, one of the most vulnerable groups in the election of human beings. A constitutional court ruling 20/ puu-xvii /2019 on the examination of the 2017 law number 7 on the elections of the constitution of the republic of Indonesia in 1945, In the context of the voting rights are highly positive and are provided with ease for those registered to the additional electoral voter (DPTB), it is not at all disadvantaged that the moving administration can proceed by 7 (seven) vote days and can use a certificate if they do not have an electronic id.